Heteroatom (P, B, or S) incorporated NiFe-based nanocubes as efficient electrocatalysts for the oxygen evolution reaction. Issue 16 (5th April 2018) - Xuan, Cuijuan; Wang, Jie; Xia, Weiwei; Zhu, Jing; Peng, Zongkai; Xia, Kedong; Xiao, Weiping; Xin, Huolin L.; Wang, Deli
Abstract : Different heteroatom incorporated NiFe-based nanocubes are synthesized with MOFs as precursors and exhibit enhanced OER activities. Abstract : Exploring low-cost and highly efficient electrocatalysts toward the oxygen evolution reaction (OER) is of significant importance, although facing great challenges for sustainable energy systems. In this work, amorphous NiFe-based porous nanocubes (Ni–Fe–O–P, Ni–Fe–O–B, and Ni–Fe–O–S) are successfully synthesized via simple and cost-effective one-step calcination of Ni–Fe based metal–organic frameworks (MOFs) and heteroatom containing molecules. The resulting three materials maintain a well-defined porous nanocube morphology with heteroatoms uniformly distributed in the structure. The unique porous structure can effectively provide more active sites and shorten the mass transport distance. Additionally, the introduction of P, B or S can tune the electronic structure, which is favorable for accelerating the charge transfer, and may lead to the formation of the higher average oxidative valence of Ni species during the OER process. Benefiting from the above desirable properties, all three materials exhibit excellent OER electrocatalytic activities and outstanding long-term stability in a home-made zinc air battery. This work not only provides a general approach for the synthesis of highly efficient electrocatalysts based on earth-abundant elements but also highlights the potential prospects of MOFs in energy conversion and storage devices.